2005
DOI: 10.2152/jmi.52.57
|View full text |Cite
|
Sign up to set email alerts
|

No association of the Trp 64 Arg mutation of the (.BETA.3-adrenergic receptor gene with obesity, type 2 diabetes mellitus, hyperlipidemia, and hypertension in Japanese patients with schizophrenia

Abstract: Objective : This study was conducted to address the question of whether the 3-adrenergic receptor gene mutation (Trp64Arg) is associated with metabolic disease in Japanese patients with schizophrenia. Methods : In a cross-sectional study, 89 participants were grouped into three genotypes. The 64 Arg allelic frequency in patients with or without metabolic disease was analyzed. Anthropometrics variables and biochemical parameters were compared among the genotypes. Results : The64Arg allele, which had a frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…There were 16 publications testing the association of ADRB3 gene Trp64Arg polymorphism with hypertension risk [ 10 , 11 , 14 , 16 , 17 , 19 , 20 , 23 31 ], incorporating 21 individual studies (3750 hypertensive patients and 4225 normotensive controls). Fourteen publications were available for the association of Trp64Arg polymorphism with blood pressure changes [ 4 , 10 , 12 15 , 17 , 18 , 21 23 , 25 , 26 , 28 ], incorporating 17 individual studies (6100 subjects). The baseline characteristics of all qualified studies are present in both Supplementary Table 1 and Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 16 publications testing the association of ADRB3 gene Trp64Arg polymorphism with hypertension risk [ 10 , 11 , 14 , 16 , 17 , 19 , 20 , 23 31 ], incorporating 21 individual studies (3750 hypertensive patients and 4225 normotensive controls). Fourteen publications were available for the association of Trp64Arg polymorphism with blood pressure changes [ 4 , 10 , 12 15 , 17 , 18 , 21 23 , 25 , 26 , 28 ], incorporating 17 individual studies (6100 subjects). The baseline characteristics of all qualified studies are present in both Supplementary Table 1 and Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the positive studies summarized above, we identified 92 studies dealing with 58 genes in which there was no evidence of associations between DNA sequence variations and obesity‐related phenotypes. Among these studies, the most frequent ones were those pertaining to markers of PPARG (1012, 1114, 1115, 1116, 1117, 1118, 1119, 1120, 1121, 1122, 1123, 1124, 1125, 1126) (14 studies), ADIPOQ (1127, 1128, 1129, 1130), ADRB3 (1084, 1121, 1131, 1132), IL6 (1129, 1133, 1134, 1135) (four studies each), and ESR1 (1136, 1137, 1138) (three studies). Other markers yielding negative findings were those related to ACE (710, 1032), ACTN (1139), ADIPOR1 (1140), ADIPOR2 (1140), ADRB1 (1132), A DRB2 (1132), AGER (1141), AHSG (1142), APOA4 (1143), APOE (1144, 1145), AR (1146), BDNF (1147), CASQ1 (1148), COL1A1 (1134), CRP (1149), ENPP1 (1150), FABP2 (1151), GNAS (1152), GNB3 (1152, 1153), GPR40 (1154), H6PD (1155), HSD11B1 (1155, 1156), ICAM1 (1157), IGF1 (1158), IL6R (1159), INS (1160, 1161), KCNJ11 (1120), KL (1146), LEP (1129), LEPR (1162), LIPC (1163), LPL (1164), LTA (964), MKKS (1165), MT‐DLOOP (1166), MTHFR (1167), MTTP (1168), NOS3 (1169, 1170), NPY (1171), NR0B2 (…”
Section: Associations With Candidate Genesmentioning
confidence: 99%
“…In Japanese patients with non-insulin-dependent diabetes mellitus, this polymorphism is associated with higher serum triglyceride levels and decreased high-density lipoprotein (HDL) cholesterol levels [17]. On the other hand, this polymorphism had no apparent effect on triglyceride levels in Japanese patients with schizophrenia [18].…”
Section: Introductionmentioning
confidence: 99%